Association between Hepatitis A seropositivity and bone mineral density in adolescents and adults: a cross-sectional study using NHANES data - Yu, Zhuowen; Hu, Gunchu; Wang, Jiajie; Li, Zhihong (São Paulo Medical Journal, 2025)
BACKGROUND: Osteoporosis, characterized by decreased bone density and increased fracture risk, imposes significant physical, psychosocial, and financial burdens. Early detection and prevention are crucial for managing osteoporosis and reducing the risk of fractures. OBJECTIVES: To investigate the relationship between Hepatitis A seropositivity and bone mineral density (BMD) in adolescents and adults and to explore the potential link between Hepatitis A infection and osteoporosis risk. DESIGN AND SETTING: This cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018 to evaluate the association between hepatitis A seropositivity and BMD in 15,693 participants. METHODS: Multivariable regression analysis was used to calculate the mean BMD and standard error for adolescents and adults, followed by an independent z-test to determine whether there was a significant difference between the seropositive and seronegative groups. RESULTS: Hepatitis A seropositive adolescents and adults had lower BMD than their seronegative counterparts, with significant differences in lumber spine (mean difference = -0.03 g/cm2, P < 0.01 for both age groups) and pelvis BMDs (mean difference = -0.02 g/cm2, P < 0.01 for the adult age groups), after adjusting for various covariates. CONCLUSIONS: This study confirmed that both adolescent and adult individuals seropositive for Hepatitis A antibodies had reduced BMD among both adolescents and adults, especially in the adult group. This finding suggests a possible link between Hepatitis A infection and risk of osteoporosis.